PERAN SECOND LINE DALAM MUSNAD AHMAD BIN HANBAL - Huda, Shokhi (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2013)
Ibn Hanbal was a great mujaddid Islam with the final work hadith titled al-Musnad. Musnad is a hadith which contains a range of devices beyond the author himself, namely: (1) the teacher as transmitter of the tradition, (2) management through the involvement of his family, and (3) generation of editing afterwards, (4) the reclassification composition for service development literature, and (5) i?râb against him. The latter two devices make the referensif Musnad rises higher. Musnad strategies are (1) the involvement of the gate-keeper as the key to unlocking the information, (2) checking the validity of data through cross-check and overtime, and (3) the transformation of information to open criticism. Musnad role in the science of hadith are (1) collection of hadith which are highest among the narrators, (2) the methodology of the strategies used; and (3) contribution to the tradition of jurisprudence. In that role there contributive involvement in the preparation of Musnad second line in an orderly manner, the addition of hadith from other sources, and updates the edition.",